Proteic isoenzymic characterization of the pathovars of xanthomonas campestris which attack cassava - Kimura, Osamu; Dianese, José Carmine (Pesquisa Agropecuaria Brasileira, 2014)
Eletrophoretic profiles of soluble protein, esterase, acid phosphatase, alkaline phosphatase, and glucose-6-phophate dehydrogenase were determined for eleven isolates of X. campestris pv. manihotis, three isolates of X. campestris pv. cassavae, and one isolate of X. campestris pv. campestris Esterase and acid phosphatase were more useful in characterizing the patovars of X. campesrris (Pammel) Dowson from cassava (M. esculenta Crantz) than total protein, alkaline phosphatase or glucose-6-phosphate dehydrogenase. Phylogenic relations were established leading to differentiation of a South American isolate from two African strains of X. campestris pv. cassavae. The similarity in isozymic patterns of the South American isolate of X. campestris pv. cassavae and those of some isolates of X. campestris pv. manihotis suggests that the former could be a yellow strain of X. campestris pv. manihotis. The isolates of X. campestris pv. manihotis could be grouped according to pathogenicity by analysing their profiles of acid phosphatase.